Kidney development and disease - Miller, Rachel K. (Springer, 2017)
Kidney Development and Disease brings together established and young investigators who are leading authorities in nephrology to describe recent advances in three primary areas of research. The first section describes the use of animal models as powerful tools for the discovery of numerous molecular mechanisms regulating kidney development. The second section focuses on nephric cell renewal and differentiation, which lead to diverse cell fates within the developing kidney, and discusses diseases resulting from the aberrant regulation of the balance between cell fate decisions. The final section concentrates on morphogenesis of the developing kidney and its maintenance after formation as well as the diseases resulting from failures in these processes. Kidney form and function have been extensively studied for centuries, leading to discoveries related to their development and disease. Recent scientific advances in molecular and imaging techniques have broadened our understanding of nephron development and maintenance as well as the diseases related to these processes.
Keywords: Kidneys -- Diseases.; Kidneys.; Kidneys -- Growth.; elektronické knihy; electronic books